Health Equity and Financial Protection Datasheets : Latin America - Bredenkamp, Caryn (World Bank, Washington, DC, 2017)
The health equity and financial protection datasheets provide a picture of equity and financial protection in the health sectors of low-and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. The tables in this report show how health outcomes, risky behaviors and health care utilization vary across asset (wealth) quintiles and periods. The quintiles are based on an asset index constructed using principal components analysis. Benefit-Incidence Analysis (BIA) shows whether, and by how much, government health expenditure disproportionately benefits the poor. The distribution of subsidies depends on the assumptions made to allocate subsidies to households. Under the constant unit cost assumption, each unit of utilization is assumed to cost the same and is equal to total costs incurred in delivering this type of service divided by the number of units of utilization.